Legionnaires Disease With Focal Neurologic Deficits and a Reversible Lesion in the Splenium of the Corpus Callosum: A Case Report and Review of the Literature. Issue 1 (January 2017) - Raybould, Jillian E.; Conroy, Megan E.; Timpone, Joseph G.; Kumar, Princy N.
Abstract : Abstract: Patients with Legionnaires pneumonia frequently present with neurologic abnormalities but normal neuroimaging findings. We present a case of a healthy 52-year-old man presenting with severe Legionella pneumonia and a unique constellation of focal neurologic deficits including bowel and bladder incontinence, hemiparesis, and ataxia with progression to somnolence. A transient lesion was identified at the splenium of the corpus callosum on magnetic resonance imaging. His recovery was marked by prolonged limb and oral apraxia, but the patient improved with an early combination antibiotic treatment and the late use of corticosteroids. To our knowledge, this is the ninth case reported in the English literature of a patient presenting with Legionnaires disease with neurologic deficits and a reversible lesion at the splenium of the corpus callosum. We present a review of the literature including previous cases, with a focus on neurologic examination, neuroimaging findings, combination antibiotic therapy, and the use of corticosteroids.